2010
DOI: 10.1021/jo902488w
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Fluorinated Heterofluorene-Containing Donor−Acceptor Systems

Abstract: A series of oligothiophene-perfluoro-9-heterofluorene donor-acceptor (DA) compounds was synthesized via a combination of nucleophilic aromatic substitution (S(N)Ar(F)) and palladium coupling reactions. These compounds are of interest as possible building blocks for materials with useful electron transport properties, since they possess relatively low LUMO energy levels of -3.3 to -3.6 eV (as determined by differential pulse voltammetry). The HOMO-LUMO energy gaps, as determined by UV-vis spectroscopy, range be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 65 publications
0
20
0
Order By: Relevance
“…We continued our synthesis by taking advantage of the S N Ar‐reactivity of perfluorobiphenyls that proceeds selectively at the 4,4′‐positions, which is desirable for extending the π‐conjugation along the long‐axis of the biphenyl skeleton. As shown in Scheme , the reaction of 2 with ethynyltriisopropylsilane (1.2 equiv.)…”
Section: Resultsmentioning
confidence: 99%
“…We continued our synthesis by taking advantage of the S N Ar‐reactivity of perfluorobiphenyls that proceeds selectively at the 4,4′‐positions, which is desirable for extending the π‐conjugation along the long‐axis of the biphenyl skeleton. As shown in Scheme , the reaction of 2 with ethynyltriisopropylsilane (1.2 equiv.)…”
Section: Resultsmentioning
confidence: 99%
“…The naphthalene ring is essentially planar, with a maximum deviation of 0.026(2) Å for atom C(3) in 1, 0.052(2) Å for atom C(10) in 2, and 0.039(2) Å for atom C(5) in 3, respectively. The bond distance of C(11)-C(12) in 1 (1.519(2) Å) is 120.9(2) 121.16 C(2)-C(1)-C (22) 133.44 (19) 132.54 C(10)-C(1)-C (22) 105.63 (18) 106.31 C(10)-C(11)-C (12) 107.39 (15) 105.89 C(10)-C(11)-C (23) 98.45 (16) 99.06 C(11)-C(23)-C (22) 94.24 (16) 94.16 Torsion angles (°) C(2)-C(1)-C(10)-C (11) 177.52 (18) 179.79 C(1)-C(10)-C(11)-C (12) 66.8 (2) 67.20 C(21)-C(22)-C(23)-C (11) 53.58 (19) 53.92 C(10)-C(1)-C(21)-C(12) 0.5(1) 0.4…”
Section: Resultsmentioning
confidence: 99%
“…[32] Tilley and coworkers reported the synthesis of a series of fluorinated heterofluorenes including germafluorene systems that exhibited high electron affinities and showed great potential as electron transporting materials. [33][34][35] A series of spirocyclic germafluorene-germoles that exhibited good photo-and thermal stability and with tunable luminescence were reported recently by Rivard and coworkers. [36] Many of the germafluorenes reported to date have been prepared by a lithium-halogen exchange reaction between a dihalobiphenyl precursor and nBuLi, followed by reaction with an appropriate dichlorogermane.…”
Section: Introductionmentioning
confidence: 99%
“…[36] Many of the germafluorenes reported to date have been prepared by a lithium-halogen exchange reaction between a dihalobiphenyl precursor and nBuLi, followed by reaction with an appropriate dichlorogermane. [31,[34][35][36][37] Recent reports have shown that transition-metal catalyzed routes can be used for the formation of germafluorene and silafluorene derivatives. [29,[38][39][40] An inexpensive, simplified, and higher yielding route to the tetra-halogenated precursor, 4,4ʹ-dibromo-2,2ʹ-diiodo-5,5ʹ-dimethoxy-1,1ʹ-biphenyl was reported by Huang et.…”
Section: Introductionmentioning
confidence: 99%